Faktor-faktor yang Mempengaruhi Loyalitas Donatur dalam Membayar ZIS pada LAZ Al Azhar Sul-Sel : Moderasi Kepercayaan - L, Nurliana; Anwar, Nurfiah; Katman, Muhammad Nasri (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The purpose of this research is to know the effect of telemarketing and transparency use through social media to donor loyalty in paying ZIS at LAZ Al Azhar Sul-Sel with trust as moderate variable. The type of research used is quantitative research with questionnaire or lift as data collection tool. Respondents in this study are the community or donor who once paid zakat, infak, and alms at LAZ Al Azhar Sul-Sel. Samples analysis using Krijie Morgan formula and research measurement using data analysis of Structural Equation Model based Patrial Least Square (SEM PLS) using the SmartPLS 3 application. The results showed that based on the analysis of the coefficient of determination (r-Square) contributed of telemarketing, transparency, and trust to donor loyalty of 60,4% while 39,6% may be influenced by other factors outside of the study. From the results of statistical shows that telemarketing has positive and significant effect on the donor loyalty in paying ZIS at LAZ Al Azhar Sul-Sel, in addition to transparency also has a positive and significant effect on donor loyalty in paying ZIS at LAZ Al Azhar Sul-Sel, while trust does not moderate telemarketing on donor loyalty in paying ZIS at LAZ Al Azhar Sul-Sel, as much as trust is not moderating transparency to donor loyalty in paying at LAZ Al Azhar Sul-Sel.